ANTARA LANGGHAR, BHAQAF, DAN SUMBER MATA AIR - R. Ahmad Nur Kholis (JURNAL PUSAKA, 2022)
The purpose of this study is to describe about architectural building called bhaqaf in the tradition of Javanese and Madura. This is a qualitative research using ethnographic research design. It conducted based on deep observation towards bhaqaf in both Pamekasan dan Malang districts. This study is also emphasized on: 1) the term of bhaqaf in Madura closes to Arabic term waqf which means stop or place where to stop; 2) architectural building of bhaqaf in Javanese and Madura culture in some cases is placed closely to water source; 3) in the past, bhaqaf often used as rest area some of people who had a long travel; 4) bhaqaf existence, in some way, also involves in Islamic fiqh which closely related to Syafi’iyah concepts of mutanajjis, musta’mal, the water level for people to do wudhu called two qullah; 5) bhaqaf is one of Islamic dakwa infrastructure which specifically become the public service place for Muslim to pray; 6) nowadays, some of bhaqaf building develops into musala.  Key words: bhaqaf, water source, culture, local wisdom, architecture.